1985
DOI: 10.1093/infdis/152.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a DNA-Hybridization Method for Detection of African and Asian Strains of Neisseria gonorrhoeae in Men with Urethritis

Abstract: The 2.6-megadalton (MDa) cryptic plasmid and the 4.4-MDa beta-lactamase plasmid of Neisseria gonorrhoeae were radiolabeled with [32P] nucleotides and used as probes for direct detection of gonococci and beta-lactamase plasmids in urethral exudates from men with urethritis. The sensitivity and specificity of the DNA probes were compared with culture isolation of N. gonorrhoeae and biochemical tests of gonococcal isolates for beta-lactamase production. Of 216 urethral specimens, 180 were positive for N. gonorrho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

1986
1986
1993
1993

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…The aminopeptidase F 16 meningococci showed a typical aminopeptidase profile that is, glutamyl aminopeptidase activity but not hydroxyproline aminopeptidare activity (table 1). The remaining three strains showed the converse, which is typical of N gonorrhoeae or N lactamica.…”
Section: Resultsmentioning
confidence: 99%
“…The aminopeptidase F 16 meningococci showed a typical aminopeptidase profile that is, glutamyl aminopeptidase activity but not hydroxyproline aminopeptidare activity (table 1). The remaining three strains showed the converse, which is typical of N gonorrhoeae or N lactamica.…”
Section: Resultsmentioning
confidence: 99%
“…The probe assay was 91% sensitive and 96% specific when compared with the chromogenic cephalosporin test performed on isolated colonies of N. gonorrhoeae (26). More studies of this type (i.e., parallel identification and susceptibility testing with probes) would be of value for determining the feasibility of probes as rapid diagnostic aids for physicians offices, outpatient clinics, and Third World countries.…”
Section: Aminoglycoside Resistance Genesmentioning
confidence: 99%
“…Five "false negatives" turned out to harbor plasmid-lacking Neisseria. Perine et al (94) detected Neisseria urethritis in urethral exudates of men with clinical symptoms of gonococcal urethritis using a similar assay and reported that 180 of 216 samples were positive by hybridization and culture; 27 were negative by both tests. Hyyp'a et al …”
Section: Sexually Transmitted Diseases and Genital Infectionsmentioning
confidence: 99%